2020
DOI: 10.1097/spv.0000000000000811
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns for Women With Overactive Bladder Syndrome: Time Between Medications and Third-Line Treatments

Abstract: Objective The aims of this study are to determine how long it takes female patients with overactive bladder (OAB) to receive third-line treatment after starting OAB medications and identify factors associated with increased time. Methods This was a retrospective observational cohort study of adult female patients with OAB who received third-line treatment between 2013 and 2015 using insurance claims databases. Primary outcome was time between first OAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The use of telehealth for urology appointments is an up and coming prospect that may improve care for OAB. 21 Kirby et al 12 found that in women with OAB seeing any care provider for treatment, the median time to thirdline therapy is greater than 3 years. At our tertiary referral center with an FPMRS fellowship-trained urologist, the mean time pre-CCP for third-line therapy was 280 days; the use of a CCP nearly halved this time to 160 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of telehealth for urology appointments is an up and coming prospect that may improve care for OAB. 21 Kirby et al 12 found that in women with OAB seeing any care provider for treatment, the median time to thirdline therapy is greater than 3 years. At our tertiary referral center with an FPMRS fellowship-trained urologist, the mean time pre-CCP for third-line therapy was 280 days; the use of a CCP nearly halved this time to 160 days.…”
Section: Discussionmentioning
confidence: 99%
“…While third‐line therapies such as sacral neuromodulation, intradetrusor onabotulinumtoxinA injections, and percutaneous tibial nerve stimulation (PTNS) are found to be more efficacious in managing OAB, a study found that only 2% of patients utilize said therapies 9–11 . Furthermore, women with OAB wait on average more than 3 years to undergo third‐line therapy 12 . Overall, patients with OAB demonstrated a poor understanding for OAB physiology, modalities of treatment, and dissatisfaction of care resulting in loss to follow‐up 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing literature on anticholinergics including the association with incident dementia has raised concern about their use. [4][5][6] Additionally, Kirby et al, 7 2020 demonstrated a relationship in the number of anticholinergics trialed and time to third line therapy. This may reflect a subset of patients with unaddressed symptoms and continued potential risks of different anticholinergics in a real-world setting.…”
mentioning
confidence: 99%
“…Data informing on the average time spent in follow-up visits specifically for the treatment of overactive bladder are largely lacking. Tai-Seale et al 14 demonstrated that in primary care setting, a median follow-up visit length was 15.7 minutes. This time frame seems to be consistent with our practice where patients with OAB are booked for 15-minute follow-up appointments.…”
Section: Discussionmentioning
confidence: 99%